Electrostatic-Aerodynamic Compression in Hypersonic Cylindrical Inlet (Communications in Computational Physics, 2008)
Hypersonic magneto-fluid-dynamic interaction has been successfully performed as a virtual leading-edge strake and a virtual cowl of a rectangular inlet. Ina side-by-side experimental and computational study, the magnitude of the inducedcompression was found to depend on configuration and electrode placement. To better understand the interacting phenomenon the present investigation is focused on adirect current discharge at the leading edge of a cylindrical inlet for which validatingexperimental data is available. The present computational result is obtained by solving the magneto-fluid-dynamics equations at the low magnetic Reynolds number limitand using a nonequilibrium weakly ionized gas model based on the drift-diffusiontheory. The numerical simulation provides a detailed description of the intriguingphysics. After validation with experimental measurements, the computed results further quantify the effectiveness of a magneto-fluid-dynamic compression for a hypersonic cylindrical inlet. A minuscule power input to a direct current surface dischargeof 8.14 watts per square centimeter of electrode area produces an additional compression of 6.7 percent for a constant cross-section cylindrical inlet.